2005
DOI: 10.1186/1471-2407-5-75
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression analysis in time series following N-acetyl L-cysteine induced epithelial differentiation of human normal and cancer cells in vitro

Abstract: Background: Cancer prevention trials using different types of antioxidant supplements have been carried out at several occasions and one of the investigated compounds has been the antioxidant N-acetyl-L-cysteine (NAC). Studies at the cellular level have previously demonstrated that a single supplementation of NAC induces a ten-fold more rapid differentiation in normal primary human keratinocytes as well as a reversion of a colon carcinoma cell line from neoplastic proliferation to apical-basolateral differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 70 publications
3
27
1
Order By: Relevance
“…However, recent work from our laboratory and those of the others established other important functions for NAC which could be the basis for its death inhibitory property [12,13]. Here we demonstrate that the basis for cell death inhibitory function of NAC could be its capacity to induce NFκB, and modulate important differentiation and activation genes in DPSCs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, recent work from our laboratory and those of the others established other important functions for NAC which could be the basis for its death inhibitory property [12,13]. Here we demonstrate that the basis for cell death inhibitory function of NAC could be its capacity to induce NFκB, and modulate important differentiation and activation genes in DPSCs.…”
Section: Discussionsupporting
confidence: 54%
“…[12,13]. In contrast, significant increases in the cell proliferation and cell numbers was seen when NAC was added to untreated and HEMA treated cells when compared to HEMA alone treated cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Three days after NAC exposure, differentiation of NHEK is demonstrated by an increased number of intracellular junctions, basal localization of actin as well as by ceased proliferation [4] . These observations could also be confi rmed by an Affymetrix gene expression analysis encompassing 12,000 gene sequences [5] .…”
Section: Introductionmentioning
confidence: 65%
“…Previous morphological and biochemical studies have indicated that NHEK, as well as the colon carcinoma cell line Caco-2, undergo an accelerated differentiation upon treatment with NAC [4,5] . In fi gure 1 , we show that NAC treatment induces cytoskeletal remodelling and formation of adherens junctions in NHEK, indicating a reversion from a proliferation state to differentiation, without affecting cell viability.…”
Section: Experimental Overviewmentioning
confidence: 99%